2020
DOI: 10.1111/cpr.12808
|View full text |Cite|
|
Sign up to set email alerts
|

Potential role of two novel agonists of thyroid hormone receptor‐β on liver regeneration

Abstract: Objectives Although the hepatomitogenic activity of triiodothyronine (T3) is well established, the wide range of harmful effects exerted by this hormone precludes its use in liver regenerative therapy. Selective agonists of the beta isoform of thyroid hormone receptor (TRβ) do not exhibit T3‐induced cardiotoxicity and show a good safety profile in patients with NASH. The aim of this study was to investigate whether two novel TRβ agonists, the prodrug TG68 and the active compound IS25 could stimulate hepatocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…As already observed in previous studies [ 22 , 23 ], the administration of TG68 in HFD-fed mice lowered the serum levels of ALT and AST, revealing that, in addition to revert a condition of simple steatosis, it may also efficiently ameliorate the background of cell death typical of NASH. Furthermore, TG68 can also significantly reduce serum TAGs.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…As already observed in previous studies [ 22 , 23 ], the administration of TG68 in HFD-fed mice lowered the serum levels of ALT and AST, revealing that, in addition to revert a condition of simple steatosis, it may also efficiently ameliorate the background of cell death typical of NASH. Furthermore, TG68 can also significantly reduce serum TAGs.…”
Section: Discussionsupporting
confidence: 77%
“…Both IS25 and TG68, when tested for cytotoxicity and ADME-Tox/off-target liability in vitro, revealed a convincing lack of toxicity and the capacity to reduce total lipid accumulation into lipid droplets with an effect comparable, or even higher, than equimolar doses of T3 [ 22 ]. Further in vivo studies showed that both compounds were able to increase hepatocyte proliferation, in a way quite similar to the thyroid hormone T3, but in the absence of liver damage, cardiotoxicity, and renal hypertrophy [ 23 ], demonstrating a marked hepato-specificity. Based on these encouraging preliminary results, we decided to investigate prodrug TG68 in a NASH mouse model in order to explore its potential to treat this liver syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Since its initial development, many analogs of GC-1 have been designed and tested for functionality, selectivity, and permeability [ 38 , 39 ]. In particular, IS25 and TG68 ( Figure 1 ) showed encouraging off-target and ADME-Tox profiles both in vitro and in vivo [ 40 , 41 ], facilitating liver proliferation and alleviating lipid metabolism disorders, without exhibiting T 3 -induced cardiotoxicity [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, TRβ-selective thyromimetics devoid of relevant side effects might find a possible use in regenerative medicine ( 83 , 96 ). Even though still at a preliminary level, ongoing studies have revealed that in F344 rats a sub-chronic treatment with the two novel TRβ-agonists, namely IS25 and TG68, induced hepatocyte proliferation in the absence of any sign of hepatic toxicity and cardiac hypertrophy ( 75 ). Notably, hepatocyte proliferation appears to be associated with activation of TR-target genes, such as Dio1 and Spot14, suggesting that the mitogenic effect of these drugs may be due to binding and activation of TRβ.…”
Section: Sobetirome and Novel Diphenylmethane Structure Based Thyromimentioning
confidence: 99%
“…Notably, hepatocyte proliferation appears to be associated with activation of TR-target genes, such as Dio1 and Spot14, suggesting that the mitogenic effect of these drugs may be due to binding and activation of TRβ. Importantly, the liver proliferative response induced by the two TRβ agonists was not associated with liver damage, as assessed by biochemical determination of serum transaminases and by immunostaining for Caspase-3, but it was the result of a direct effect of these drugs enabling quiescent hepatocytes to re-entry into the cell cycle ( 75 ). Hence these newly developed agents may have a significant clinical application for hepatic regenerative therapies or other surgical procedures.…”
Section: Sobetirome and Novel Diphenylmethane Structure Based Thyromimentioning
confidence: 99%